Analysis of the Impact of Gamification, User Experience, and Service Quality on Customer Engagement Levels on The Indonesia E-Commerce Platform - Saiful Bahri; Vio Ariawan (Universal Business and Management Review, 2026)
This study aims to analyze the effect of gamification implementation, user experience (UX), and service quality on customer engagement on the Shopee e-commerce platform among teenagers. The increasing use of e-commerce platforms by the younger generation requires strategies that can build sustainable customer engagement through interactive features and superior service quality. This study uses a quantitative approach with a survey method, with a total of 94 respondents selected through purposive sampling. Data analysis was performed using multiple linear regression with the help of SPSS software. The results showed that gamification, UX, and service quality had a positive and significant effect on customer engagement. These findings indicate that game-based features, easy and enjoyable user experiences, and reliable and efficient services can simultaneously increase customer engagement on e-commerce platforms. This study provides practical implications for e-commerce players in designing interactive and high-quality strategies to maintain consumer loyalty, especially among the youth segment. The limitations of this study lie in the use of cross-sectional data and the limited scope of the sample, so the generalization of the research results still needs to be further examined.